MORPHOLOGICAL ASPECTS OF THE STRUCTURE OF THE UTERUS IN WHITE OUTBRED RATS - Ishankulova Dildora Khabibullaevna; Ikhtiyarova Gulchexra Akmalovna; Ilyasov Aziz Saidmuratovich (Scholar Express Journals, 2024)
Using light microscopy methods, the morphological structure of the uterus in white outbred rats was clarified. It was found that the walls of the uterine horns grow together, forming a double body and neck, which are separated from each other by a thin septum and have two separate openings in the vagina. The medial walls unite the perimeter and the supravascular layer of the myometrium at the confluence. These results can be used to write sections of evolutionary, functional, comparative species morphology and reproductive biology. The cervix of white outbred rats is more similar to humans, which should be taken into account when choosing an experimental model for scientific research.
Keywords: uterus; cervix; myometrium; morphology